Innate and Adaptive Lymphocytes in Non-Tuberculous Mycobacteria Lung Disease: A Review - Gramegna, Andrea; Lombardi, Andrea; Lorè, Nicola I.; Amati, Francesco; Barone, Ivan; Azzarà, Cecilia; Cirillo, Daniela; Aliberti, Stefano; Gori, Andrea; Blasi, Francesco (Frontiers in Immunology, 2022)
Non-tuberculous mycobacteria (NTM) are ubiquitous environmental microorganisms capable of a wide range of infections that primarily involve the lymphatic system and the lower respiratory tract. In recent years, cases of lung infection sustained by NTM have been steadily increasing, due mainly to the ageing of the population with underlying lung disease, the enlargement of the cohort of patients undergoing immunosuppressive medications and the improvement in microbiologic diagnosis. However, only a small proportion of individuals at risk ultimately develop the disease due to reasons that are not fully appreciated. A better understanding of the pathophysiology of NTM pulmonary disease is the key to the development of better diagnostic tools and therapeutic targets for anti-mycobacterial therapy. In this review, we cover the various types of interaction between non-tuberculous mycobacteria and lymphoid effectors of innate and adaptive immunity. We also give a brief look into the mechanism of immune exhaustion, a phenomenon of immune dysfunction originally reported for chronic viral infections and tumours, but recently also observed in the setting of mycobacterial diseases. We try to set the scene to postulate that a better knowledge of immune exhaustion can play a crucial role in establishing prognostic/predictive factors and enabling a broader investigation of immune-modulatory drugs in the experimental treatment of mycobacterial pulmonary disease.